2020
DOI: 10.1097/j.jcrs.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance after bilateral toric extended depth-of-focus IOL exchange targeted for micromonovision

Abstract: Purpose: To evaluate overall patient satisfaction, spectacle independence, binocular visual acuity, rotational stability, prevalence of optical phenomena, and decentration and tilt after bilateral toric extended depth-of-focus intraocular lens (EDOF IOL) implantation targeted for micromonovision. Setting: Department of Ophthalmology, Hanusch Hospital, Vienna, Austria. Design: Prospective case series. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
4
4
1
Order By: Relevance
“…10,11,15 The binocular UIVA results are similar in our study, and the difference of 0.06 to 0.03 logMAR is, in our opinion, not clinically relevant. 10,15 Concerning the binocular UNVA at 40 cm, the aforementioned studies reported better results when compared with our study (ranging from 0.09 logMAR to 0.152 logMAR). 10,11,15 The Eyhance is marketing itself as an enhanced monofocal and not EDoF IOL, this better accurately depicts the Eyhance IOL.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…10,11,15 The binocular UIVA results are similar in our study, and the difference of 0.06 to 0.03 logMAR is, in our opinion, not clinically relevant. 10,15 Concerning the binocular UNVA at 40 cm, the aforementioned studies reported better results when compared with our study (ranging from 0.09 logMAR to 0.152 logMAR). 10,11,15 The Eyhance is marketing itself as an enhanced monofocal and not EDoF IOL, this better accurately depicts the Eyhance IOL.…”
Section: Discussionsupporting
confidence: 83%
“…10,15 Concerning the binocular UNVA at 40 cm, the aforementioned studies reported better results when compared with our study (ranging from 0.09 logMAR to 0.152 logMAR). 10,11,15 The Eyhance is marketing itself as an enhanced monofocal and not EDoF IOL, this better accurately depicts the Eyhance IOL. The TECNIS Eyhance (Johnson & Johnson) is an enhanced monofocal IOL design which is promising added intermediate vision but with a monofocal disturbance profile.…”
Section: Discussioncontrasting
confidence: 47%
“…3 An important feature of our study was the use of digital axis marking (Callisto, Carl Zeiss Meditec AG) in every case to differentiate postoperative rotation from surgical misalignment. 11,12 In our comparison of the 2 most common monofocal TIOL models in the United States—647 eyes with ZCT TECNIS IOL (Johnson & Johnson Vision) and 626 eyes with AcrySof IOL (Alcon Laboratories, Inc.)—significantly more TECNIS than AcrySof TIOLs were more than 5 (18.2% vs 8.1%, P < .0001), more than 10, and more than 15 degrees misaligned.…”
mentioning
confidence: 85%
“…A study of 52 eyes with Symfony toric IOLs using digital marking reported mean rotation of 3.5 ± 3.5 degrees. 11 Both of these SPA foldable PCIOLs use the same platforms as their monofocal counterparts with the exception of the diffractive optic. This study expands our previous TIOL study to include all monofocal and PC-TIOLs implanted from September 2016 to January 2019 to compare the rotational stability and repositioning rates of both monofocal and PC-TIOLs.…”
mentioning
confidence: 99%
“…For two of the EDOF IOLs available on the market, the use of mini-monovision has been found to significantly improve uncorrected binocular visual acuity and spectacle independence. [4][5][6][7][8][9][10][11][12][13][14][15][16] Isopure® is a hydrophobic aspheric non-diffractive IOL. Its EDOF properties are based on a polynomial surface design across the full optic providing a high amount of negative spherical aberrations, smoothly increasing from the center to the periphery of the optic.…”
Section: Introductionmentioning
confidence: 99%